Comparative Effect of Grated Coconut (Cocos nucifera, L.) on the Characteristics of Ladu Cake - Risa Meutia Fiana; Novelina Novelina; Rezy Gusmita (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2021)
Ladu cake is a traditional cake originating from the Pariaman area which has a savory and crunchy taste and a unique shape. This study aims to determine the effect of the ratio of dry grated coconut on the characteristics of the Ladu cake, to determine the effect of the best comparison level in producing the best product and to determine the storage time of the best Ladu cake. This study was designed using a completely randomized design (CRD) with 5 treatments (comparison of rice flour and dry grated coconut 100%:0%; 95%:5%; 90%:10%; 85%:15%; and 80%:20 %) and 3 replicates. The results showed that the ratio of dry grated coconut had an effect on moisture content, ash content, fat content, carbohydrate content, crude fiber content, friability, color, aroma, texture and taste. However, it had no significant effect on protein levels. Based on the chemical, physical and sensory characteristics of the comparison of Ladu cake products, the best product was obtained in the 10% dry grated coconut and 90% rice flour treatment with the characteristics of this treatment being 1.96% water content, 2.42% ash content, fat content 19.55%, protein content 7.56%, carbohydrate content 68.86%, crude fiber content 2.73%, and the average value of sensory analysis of aroma 3.70, color 4.07, texture 3.53 and taste 3.97.